Preparation method of retarded shrinkage alkali-activated slag-calcined coal gangue cement
By using slag, calcined coal gangue fine powder and calcium carbonate whiskers, combined with water glass solution, sodium hydroxide and sodium carbonate mixed alkaline excitation agent prepared, the problem of short set time and large shrinkage of alkali-activated cement is solved, and the problem of short set time and large shrinkage of alkali-activated cement is achieved. Mechanical performance improvement and shrinkage control are suitable for applications in the field of building materials.
Patent Information
- Application Number
- CN202411583280.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
AI Technical Summary
The short set time and large shrinkage of alkali-induced cement limit its large-scale application in the field of building materials.
Using slag, calcined coal gangue fine powder and calcium carbonate whiskers as raw materials, combined with water glass solution, sodium hydroxide and sodium carbonate mixed alkaline exciter prepared, adjusting the content of each component and the replacement rate of calcium carbonate whiskers , prepare the retarded alkali-reduced alkali-enhancing slag-calcined coal gangue cement.
It achieves the extended set time of alkali-excited cement, improves mechanical properties, and effective control of drying and shrinking and self-contracting, meets the set time standards of ordinary silicate cement, and has high compressive strength.
Smart Images

Figure BDA0005123683380000091 
Figure BDA0005123683380000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete materials, and in particular relates to a method for preparing slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement. Background Art
[0002] Cement is one of the indispensable building materials for the construction and development of our contemporary society. The CO2 emissions from cement production account for 5% to 7% of the total global anthropogenic CO2 emissions. While cement production brings economic benefits, the huge energy consumption and large amounts of CO2, dust and toxic gases produced during its production also put tremendous pressure on the environment. How to scientifically develop and effectively apply carbon emission reduction technologies in the cement industry is an urgent and arduous task currently facing us. Finding a sustainable material that complies with the major strategy of developing a resource-circulating economy is an effective way to achieve a low-cost, green alternative to cement.
[0003] As one of the new green cementitious materials, alkali-activated cement has attracted continuous attention from scholars and engineering circles at home and abroad for its remarkable characteristics of solid waste disposal, energy conservation and emission reduction. Alkali-activated cement is a non-traditional cementitious material obtained by alkali-activating active silica-alumina raw materials at room temperature or high temperature. The concrete prepared with it is superior to ordinary Portland cement concrete in terms of mechanical properties, high temperature resistance, impermeability and durability. However, the problems of fast coagulation and hardening and large shrinkage of alkali-slag cement have greatly limited its large-scale engineering application. The initial setting time of alkali-slag cement is generally 10-30 minutes, which is far lower than the standard requirements of the cement industry (more than 45 minutes) and does not meet the requirements of on-site construction. In addition, the shrinkage of alkali-slag cement is about 3-5 times that of ordinary Portland cement. The volume shrinkage causes the concrete to easily deform unevenly, which in turn causes microcracks on the surface of the material, affecting the mechanical properties and durability of alkali-activated cement.
[0004] Therefore, if the retarding and shrinkage reduction of alkali-activated cement can be effectively controlled, it will be beneficial to the promotion and application of this material in the field of building materials and save resources and energy. The development of retarding and shrinkage-reducing alkali-activated cement suitable for engineering applications has urgent and far-reaching significance for its promotion and application in the field of building materials. Summary of the invention
[0005] The large-scale application of alkali-activated cement still has certain limitations, especially the problem that alkali-activated slag cement sets and hardens quickly but shrinks greatly. Based on this, the present invention proposes a preparation method of slow-setting and reduced-shrinkage alkali-activated slag-calcined coal gangue cement. The method not only meets the setting time standard of ordinary Portland cement, can improve the mechanical properties of alkali-activated slag-calcined coal gangue cement, but also can effectively alleviate its drying shrinkage and autogenous shrinkage.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical purposes: a slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement, comprising the following raw materials: slag, calcined coal gangue fine powder, calcium carbonate whiskers and a mixed alkaline activator; wherein the mixed alkaline activator is prepared by mixing water glass solution, sodium hydroxide and sodium carbonate.
[0008] The present invention uses slag powder, calcined coal gangue fine powder and calcium carbonate whiskers as powder materials; then an alkaline activator prepared by water glass solution (Na2O2·4SiO2), sodium hydroxide (NaOH, solid) and sodium carbonate (Na2CO3, solid) is added to prepare slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement. The present invention changes the content of each component of the ternary mixed alkaline activator of water glass-sodium hydroxide-sodium carbonate based on the single centroid method, and finds the optimal ratio of setting time on the basis of ensuring the mechanical properties of alkali-activated cement. Then, the shrinkage of alkali-activated cement is controlled by internally adding calcium carbonate whiskers (replacing slag), and finally the optimal ratio parameters of slow-setting and shrinkage-reducing alkali-activated cement are determined. The present invention effectively solves the problems of short setting time and large shrinkage of alkali-activated cement, and is expected to realize large-scale engineering application of alkali-activated cement.
[0009] Furthermore, the mass ratio of the slag to the calcined coal gangue fine powder is (70-85): (15-30); and / or
[0010] The replacement rate of the calcium carbonate whisker for slag is 3-12wt%. The replacement rate of the calcium carbonate whisker for slag is calculated as follows: the amount of calcium carbonate whisker added / (the expected amount of slag added+the amount of calcined coal gangue fine powder added+the amount of calcium carbonate whisker added)×100%;
[0011] The actual addition amount of the slag, calcined coal gangue fine powder and calcium carbonate whisker is calculated as follows: first, the expected addition amount of slag and the addition amount of calcined coal gangue fine powder are calculated according to the mass ratio of slag to calcined coal gangue fine powder, then the addition amount of calcium carbonate whisker is calculated according to the replacement rate of calcium carbonate whisker to slag, and then the addition amount of calcium carbonate whisker is subtracted from the expected addition amount of slag to obtain the actual addition amount of slag.
[0012] Furthermore, the parameters of the slag are: density 2.5-3.0g / cm 3 , specific surface area 610-630m 2 / kg, CaO content 30-40%, SiO2 content 25-35%; and / or
[0013] The preparation method of the calcined coal gangue fine powder is as follows: washing, crushing and ball milling the original coal gangue to obtain coal gangue fine powder with a particle size of less than 0.075 mm, placing the powder in a box-type resistance furnace, heating it to 750° C. at 5° C. / min, and then keeping the temperature for 4 hours, and then sieving it through a 200-mesh square hole sieve after cooling; and / or
[0014] The parameters of the calcium carbonate whiskers are: relative density 2.5-3.0g / cm 3 , aspect ratio 20-30, CaO content 80-90%, elastic modulus 650-750GPa.
[0015] Furthermore, the amount of the mixed alkaline activator is 65-75% of the total mass of the slag and calcined coal gangue fine powder.
[0016] Furthermore, the preparation method of the mixed alkaline activator is:
[0017] Add sodium hydroxide to the water glass solution and stir to fully dissolve it;
[0018] Add sodium carbonate to water and stir to fully dissolve;
[0019] Mix the two solutions to obtain a mixed alkaline activator, which can be used after standing for more than 24 hours.
[0020] Further, the parameters of the water glass solution are: modulus 2.4, chemical composition of 32.35% SiO2, 13.73% Na2O and 53.92% H2O; and / or
[0021] The sodium hydroxide is analytically pure, with a NaOH content of ≥96%; and / or
[0022] The sodium carbonate is analytically pure, with a Na2CO3 content of ≥99.8%; and / or
[0023] The mass ratio of the sodium carbonate, sodium hydroxide and water glass solution is (32-39): (2-4): (59-66).
[0024] Technical purpose 2: A method for preparing slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement, comprising the following steps:
[0025] Slag, calcined coal gangue fine powder and calcium carbonate whisker are put into a mixer and dry-mixed until uniformly mixed, then a mixed alkaline activator is added and continued to be stirred uniformly, and the obtained cement paste is solidified and cured to obtain slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement.
[0026] Technical purpose three: Application of a slow-setting, shrinkage-reducing alkali-activated slag-calcined coal gangue cement in the field of building materials.
[0027] Compared with the prior art, the present invention has the following advantages and technical effects:
[0028] The present invention uses slag, calcined coal gangue fine powder, calcium carbonate whiskers and mixed alkaline activator as raw materials, which not only promotes the resource utilization of coal gangue, but also prepares a slow-setting and shrinkage-reducing cement-based material suitable for practical engineering applications. The setting time of the slow-setting and shrinkage-reducing cement-based material meets the setting time standard of ordinary silicate cement, has good mechanical properties and small shrinkage. If it can be widely used in the engineering field, it can create good economic value and be beneficial to environmental protection.
[0029] The slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement provided by the present invention has initial and final setting times of 412 minutes and 429 minutes respectively, a 28-day compressive strength of 102.2 MPa, and effectively reduced 49-day drying shrinkage and autogenous shrinkage. DETAILED DESCRIPTION
[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0031] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0035] The invention provides a slow-setting and shrinkage-reducing alkali-activated slag-calcined gangue cement, comprising the following raw materials: slag, calcined gangue fine powder, calcium carbonate whiskers and a mixed alkaline activator; wherein the mixed alkaline activator is prepared by mixing water glass solution, sodium hydroxide and sodium carbonate.
[0036] The addition of Na2CO3 into the mixed alkaline activator not only makes the CO3 2- With Ca 2+ The preferred reaction generates CaCO3 which is coated on the slag surface to prevent Ca 2+ Further dissolution and reduced the Ca 2+ The concentration effectively prolongs the setting time of alkali-activated cement and can generate crystalline materials, which has a certain inhibitory effect on shrinkage. Calcium carbonate whiskers can act as a "support phase" to improve compressive strength, and on the other hand, they can act as a "restricting phase" to limit shrinkage and crack development. Calcium carbonate whiskers micro-enhance the material through whisker bridging, crack deflection, whisker extraction, whisker-matrix joint extraction and whisker fracture, significantly improving the performance of alkali-activated cement.
[0037] In some preferred embodiments of the present invention, the mass ratio of slag to calcined coal gangue fine powder is (70-85):(15-30). Preferably, the product performance is optimal when the mass ratio of slag to calcined coal gangue fine powder is 3:1.
[0038] The replacement rate of the calcium carbonate whisker for slag is 3-12wt%. When the calcium carbonate whisker replaces 3-12% of the slag by mass, the product performance is optimal when the mass ratio of the total mass of slag + calcium carbonate whisker to the calcined coal gangue fine powder is 3:1. It is further preferred that the calcium carbonate whisker replaces 3% of the slag by mass.
[0039] In the following preferred embodiments of the present invention, the parameters of the slag are: density 2.5-3.0g / cm 3 , specific surface area 610-630m 2 / kg, CaO content 30-40%, SiO2 content 25-35%. The preparation method of the calcined coal gangue fine powder is: wash, crush and ball mill the original coal gangue to obtain coal gangue fine powder with a particle size of <0.075mm, place it in a box-type resistance furnace and heat it to 750℃ at 5℃ / min, then keep it warm for 4h, and sieve it through a 200-mesh square hole sieve after cooling. The parameters of the calcium carbonate whisker are: relative density 2.5-3.0g / cm 3, aspect ratio 20-30, CaO content 80-90%, elastic modulus 650-750GPa.
[0040] In the following preferred embodiments of the present invention, the amount of the mixed alkaline activator is 65-75% of the total mass of slag, calcined coal gangue fine powder and calcium carbonate whisker. In the following embodiments of the present invention, the influence of the amount of the mixed alkaline activator on the cement performance is not discussed. For example, in the following embodiments of the present invention, the amount of the mixed alkaline activator is limited to 70% of the total mass of slag, calcined coal gangue fine powder and calcium carbonate whisker. The preparation method of the mixed alkaline activator is: add sodium hydroxide to water glass solution, stir to fully dissolve it; add sodium carbonate to water, stir to fully dissolve it; mix the two solutions to obtain the mixed alkaline activator, and let it stand for more than 24 hours before use.
[0041] The parameters of the water glass solution are as follows: modulus 2.4, chemical composition 32.35% SiO2, 13.73% Na2O and 53.92% H2O; the sodium hydroxide is analytically pure, with a NaOH content of ≥96%; the sodium carbonate is analytically pure, with a Na2CO3 content of ≥99.8%; the mass ratio of the sodium carbonate, sodium hydroxide and water glass solution is (32-39): (2-4): (59-66). For example, (32-39): 2: (59-66); (32-39): 4: (59-66); 32: (2-4): (59-66); 39: (2-4): (59-66); (32-39): (2-4): 59; (32-39): (2-4): 66. In the examples of the present invention, the influence of the water-binder ratio in the mixed alkaline activator on the cement performance is not discussed. For example, in the following examples, the solid content of the prepared mixed alkaline activator is uniformly set to 40 wt%.
[0042] The preparation method of the slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement comprises the following steps:
[0043] Slag, calcined coal gangue fine powder and calcium carbonate whisker are put into a mixer and dry-mixed until uniformly mixed, then a mixed alkaline activator is added and continued to be stirred uniformly, and the obtained cement paste is solidified and cured to obtain slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement.
[0044] The slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement can be used as a building material.
[0045] The main chemical components of slag powder, calcined coal gangue fine powder and calcium carbonate whisker in the embodiment of the present invention are shown in Table 1 in terms of mass percentage.
[0046] Table 1 Chemical composition of slag powder, calcined coal gangue fine powder and calcium carbonate whisker (wt%)
[0047] raw materials CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO <![CDATA[SO3]]> <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[Fe2O3]]> MnO <![CDATA[TiO2]]> LOI slag 38.42 30.01 16.5 9.56 2.53 0.38 0.35 0.49 0.25 1.1 0.06 Calcined coal gangue fine powder 0.79 58.42 28.32 0.48 0.33 1.9 0.21 7.92 0.11 1.03 0.03 Calcium carbonate whiskers 89.75 4.71 0.32 3.76 0.08 0.09 0.42 0.5 0.27 - 0.04
[0048] Note: LOI stands for loss on ignition.
[0049] The "room temperature" mentioned in the present invention refers to 25±2°C unless otherwise specified.
[0050] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.
[0051] The raw materials used in the present invention are all purchased from the market.
[0052] The performance testing methods involved in the following embodiments of the present invention are as follows:
[0053] (1) Fluidity
[0054] The fluidity of alkali-activated cement was measured with reference to GB / T8077-2000 "Test Method for Homogeneity of Concrete Admixtures". Take 300g of powder, add the mixed alkaline activator and stir into a pure paste. Pour the uniformly stirred paste into a metal round mold, lift it vertically, and record the maximum diameters of the alkali-activated cement in two vertical directions after free flow on the horizontal glass plate for 30s. The average of these two numbers is the fluidity of the alkali-activated cement.
[0055] (2) Setting time
[0056] With reference to GB / T 1346-2011 “Test methods for water consumption, setting time and stability of cement of standard consistency”, the initial setting time and final setting time of alkali-activated cement were measured using a Vicat apparatus.
[0057] (3) Compressive strength
[0058] With reference to GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)", the size of the specimen mold is 40mm×40mm×40mm. After the specimen is formed, the surface is covered with a layer of plastic wrap and placed at room temperature for 24 hours before demoulding. The demoulded clean slurry specimen is wrapped with plastic film for curing at a curing environment temperature of 25±2℃. After the clean slurry specimen is cured to the test age, the compressive strength test is carried out on it using a YAW-2000 microcomputer-controlled electro-hydraulic servo universal press at a loading speed of 0.4MPa / s.
[0059] (4) Drying shrinkage
[0060] Three test blocks with specifications of 25mm×25mm×280mm were prepared in each group. After one day of molding, the test pieces were demoulded and the initial length L0 of the test pieces was measured. The test pieces were then placed in a drying and curing box at T=25±2℃, RH=60% for curing. When measuring, the comparator was placed on the workbench, the standard rod was placed in the spherical holes of the upper and lower probes of the comparator, and the "0" position on the dial of the micrometer was adjusted to align with the pointer of the micrometer. After the test piece was wiped clean, it was placed steadily in the upper and lower grooves of the comparator bracket, and then the micrometer reading was read every 24 hours, recorded as △L. The drying shrinkage rate calculation formula is shown in formula (1):
[0061] ε=△L / L0 (1)
[0062] (5) Autogenous shrinkage
[0063] The shrinkage test uses the MCU-32 distributed modular automatic measurement unit and VWS-10 vibrating wire strain gauge produced by Nanjing Genan Industrial Co., Ltd. (basic parameters are shown in Table 2). The freshly mixed slurry is placed in an oiled Φ100mm×250mm PVC plastic test mold, and the vibrating wire strain gauge is buried in the middle of the specimen. After pouring, the surface of the specimen is immediately sealed with epoxy resin to ensure that the concrete specimen is in an absolute moisture state. The molded specimen is placed in an environment of 30±2℃ for curing, and a data acquisition device is used to track the shrinkage deformation of concrete at different ages. The strain variable ε is calculated according to formula (2):
[0064] Table 2 Specifications and main technical parameters of VWS-10 vibrating wire strain gauge
[0065]
[0066] ε=k(F-F0)+b(T-T0) (2)
[0067] Where: ε is the strain of the structure being measured, in μm / m; k is the measurement sensitivity of the strain gauge, in 10 -6 / F; F—real-time measurement value of the strain gauge, in F; F0—reference measurement value of the strain gauge, in F; b—temperature correction coefficient of the strain gauge, determined by the manufacturer as b=13.5(10 -6 / ℃); T—real-time measurement value of temperature, in ℃; T0—measurement reference value of temperature, in ℃.
[0068] The technical solution of the present invention is further illustrated by the following embodiments.
[0069] In order to evaluate the effect of mixed alkaline activator on the fluidity, setting time and compressive strength of alkali activated cement, in Example 1-16 of the present invention, the mixed alkaline activator was first mixed with slag and calcined coal gangue fine powder to prepare alkali activated slag-calcined coal gangue cement, wherein the mass ratio of slag to calcined coal gangue fine powder was 3:1.
[0070] Example 1
[0071] Preparation of alkali activated slag-calcined coal gangue cement:
[0072] (1) Preparation of mixed alkaline activator: 30 g of sodium carbonate solid was dissolved in 22.26 g of water, and then 70 g of water glass solution was added. After stirring evenly, a mixed alkaline activator was obtained, which was sealed and allowed to stand for 24 h before use.
[0073] (2) Preparation of calcined coal gangue fine powder: The original coal gangue is washed, crushed and ball-milled to obtain coal gangue fine powder with a particle size of less than 0.075 mm, placed in a box-type resistance furnace and heated to 750° C. at 5° C. / min and then kept warm for 4 h. After cooling, it is sieved through a 200-mesh square hole sieve to obtain calcined coal gangue fine powder;
[0074] (3) 75 g of slag and 25 g of calcined coal gangue fine powder were added into a mixer and mixed evenly, and then 70 g of mixed alkaline activator was added and stirred evenly to form cement slurry;
[0075] (4) injecting the cement slurry into a mold for solidification, demolding, and sealing and curing at 35° C. for 28 days to obtain the alkali-activated slag-calcined coal gangue cement.
[0076] Example 2
[0077] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 30 g of sodium carbonate solid in 25.40 g of water, dissolving 10 g of sodium hydroxide solid in 60 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0078] Example 3
[0079] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 30 g of sodium carbonate solid in 28.54 g of water, dissolving 20 g of sodium hydroxide solid in 50 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0080] Example 4
[0081] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 40 g of sodium carbonate solid in 30.79 g of water, dissolving 10 g of sodium hydroxide solid in 50 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0082] Example 5
[0083] The same as Example 1, except that the mixed alkaline activator in step (1) is prepared by dissolving 50 g of sodium carbonate solid in 33.04 g of water, adding 70 g of water glass solution, stirring evenly to obtain a mixed alkaline activator, and sealing and standing for 24 hours before use.
[0084] Example 6
[0085] The same as Example 1, except that the mixed alkaline activator in step (1) is prepared by dissolving 40 g of sodium carbonate solid in 27.65 g of water, adding 60 g of water glass solution, stirring evenly to obtain a mixed alkaline activator, and sealing and standing for 24 hours before use.
[0086] Example 7
[0087] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 36 g of sodium carbonate solid in 28.00 g of water, dissolving 8 g of sodium hydroxide solid in 56 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0088] Example 8
[0089] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 46 g of sodium carbonate solid in 31.51 g of water, dissolving 2 g of sodium hydroxide solid in 52 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0090] Example 9
[0091] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 39 g of sodium carbonate solid in 29.94 g of water, dissolving 9 g of sodium hydroxide solid in 52 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0092] Example 10
[0093] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 32 g of sodium carbonate solid in 28.36 g of water, dissolving 16 g of sodium hydroxide solid in 52 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0094] Embodiment 11
[0095] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 42 g of sodium carbonate solid in 29.98 g of water, dissolving 4 g of sodium hydroxide solid in 54 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0096] Example 12
[0097] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 34 g of sodium carbonate solid in 28.18 g of water, dissolving 12 g of sodium hydroxide solid in 54 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0098] Example 13
[0099] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 39 g of sodium carbonate solid in 27.74 g of water, dissolving 2 g of sodium hydroxide solid in 59 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0100] Embodiment 14
[0101] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 32 g of sodium carbonate solid in 26.17 g of water, dissolving 9 g of sodium hydroxide solid in 59 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0102] Embodiment 15
[0103] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 34 g of sodium carbonate solid in 25.67 g of water, dissolving 4 g of sodium hydroxide solid in 62 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0104] Example 16
[0105] The same as Example 1, except that, in step (1), the mixed alkaline activator is prepared by dissolving 32 g of sodium carbonate solid in 23.96 g of water, dissolving 2 g of sodium hydroxide solid in 66 g of water glass solution, mixing the two solutions and stirring them evenly to obtain a mixed alkaline activator, which is then sealed and allowed to stand for 24 hours before use.
[0106] In the process of preparing the alkali-activated slag-calcined coal gangue cement of Examples 1-16, the data of fluidity, initial setting time, final setting time and 28-day compressive strength of the alkali-activated slag-calcined coal gangue cement are recorded and shown in Table 3.
[0107] Table 3 Performance test results of alkali activated slag-calcined coal gangue cement prepared in Examples 1-16
[0108] Fluidity / mm Initial setting time / min Final setting time / min 28-day compressive strength / MPa Example 1 122 1229 1258 93.3 Example 2 176 27 38 86.7 Example 3 182 24 35 105 Example 4 182 26 41 89.9 Example 5 134 2371 2408 75.5 Example 6 123 1968 2013 84.2 Example 7 179 30 41 90.1 Example 8 149 996 1068 83.7 Example 9 190 29 37 92.5 Example 10 198 25 33 102.3 Embodiment 11 169 72 85 87.3 Example 12 188 26 32 95.8 Example 13 146 346 369 86.9 Embodiment 14 189 34 45 88.9 Embodiment 15 162 113 134 88.9 Example 16 146 334 346 95
[0109] The cement prepared by the present invention should meet the requirements of ordinary Portland cement for setting time, that is, the standards of initial setting time ≥45min and final setting time ≤600min, and on this basis, the cement strength is selected from the embodiment with higher strength. Therefore, it can be seen from Table 3 that the alkali-activated slag-calcined coal gangue cement prepared by using the mixed alkaline activators of Examples 13, 15 and 16 of the present invention not only has a setting time that meets the construction strength, but also has a higher compressive strength. It can also be found that the change in the content of each component in the ternary mixed alkaline activator of water glass-sodium hydroxide-sodium carbonate will affect the length of the setting time and the size of the compressive strength of the alkali-activated cement.
[0110] Comprehensive analysis shows that the alkali-activated slag-calcined coal gangue cement prepared by the method of Example 16 has the best performance. Therefore, the mixed alkaline activator in Example 16 is used as the basis for subsequent experiments.
[0111] Embodiment 17
[0112] Preparation of a slow-setting, shrinkage-reducing alkali-activated slag-calcined coal gangue cement:
[0113] (1) Preparation of mixed alkaline activator: 32 g of sodium carbonate solid was dissolved in 23.96 g of water, and 2 g of sodium hydroxide solid was dissolved in 66 g of water glass solution. The two solutions were mixed and stirred to obtain a mixed alkaline activator, which was sealed and allowed to stand for 24 h before use;
[0114] (2) Put 100g of slag into a slurry mixer and stir evenly;
[0115] (3) Pour 70 g of the mixed alkaline activator into a slurry mixer and continue to stir evenly. Inject the obtained cement slurry into a mold for solidification, demoulding, and sealing and curing at 35° C. for 28 days to obtain slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement.
[0116] Embodiment 18
[0117] Same as Example 17, except that step (2) is: 75 g of slag and 25 g of calcined coal gangue fine powder are put into a slurry mixer and stirred evenly.
[0118] Embodiment 19
[0119] The same as Example 17, except that step (2) is: 72 g of slag, 25 g of calcined coal gangue fine powder and 3 g of calcium carbonate whisker are put into a slurry mixer and stirred evenly.
[0120] Embodiment 20
[0121] The same as Example 17, except that step (2) is: 69 g of slag, 25 g of calcined coal gangue fine powder and 6 g of calcium carbonate whisker are put into a slurry mixer and stirred evenly.
[0122] Embodiment 21
[0123] Same as Example 17, except that step (2) is: 66 g of slag, 25 g of calcined coal gangue fine powder and 9 g of calcium carbonate whisker are put into a slurry mixer and stirred evenly.
[0124] Embodiment 22
[0125] Same as Example 17, except that step (2) is: 63 g of slag, 25 g of calcined coal gangue fine powder and 12 g of calcium carbonate whisker are put into a slurry mixer and stirred evenly.
[0126] In the process of preparing the slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement of Examples 17-22, the data of fluidity, initial setting time, final setting time, 28-day compressive strength, 49-day drying shrinkage and 49-day autogenous shrinkage of the alkali-activated slag-calcined coal gangue cement are recorded and shown in Table 4.
[0127] Table 4 Performance test results of slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement prepared in Examples 17-22
[0128]
[0129] Comparing the data of Example 17 and Example 18, it can be seen that the addition of calcined coal gangue fine powder reduces the fluidity of alkali-activated cement, prolongs the setting time, improves the mechanical properties, and reduces shrinkage. The fluidity of Example 18 was reduced from 154mm to 146mm. The initial setting time increased from 257min to 334min, and its final setting time increased from 269min to 346min. The 28d compressive strength increased from 85.2MPa to 95MPa, an increase of 11.5%. The 49d drying shrinkage of Example 18 was reduced from 11590μm / m to 8310μm / m, and the autogenous shrinkage was reduced from 3745μm / m to 2924μm / m. The addition of calcined coal gangue fine powder increases the Al / Si ratio of the system, helps to form two products, NASH and CASH. The two gels are cross-linked with each other, which helps to fill the gaps between different reaction stages and unreacted particles, making the structure more compact, thereby improving the mechanical properties of the material.
[0130] Comparing the data of Examples 18-22, it can be seen that with the increase of the replacement rate of calcium carbonate whiskers (the replacement rates of calcium carbonate whiskers for slag in Examples 18-22 are 0wt%, 3wt%, 6wt%, 9wt%, and 12wt%, respectively), the fluidity of alkali-activated cement decreases, the setting time is prolonged, the mechanical properties and drying shrinkage show a trend of first increasing and then decreasing, and the autogenous shrinkage decreases. The initial setting time of Example 19 increases from 334min to 412min, and its final setting time increases from 346min to 429min. The 28d compressive strength increases from 95MPa to 102.2MPa, an increase of 7.58%. The 49d drying shrinkage rate decreases from 8310μm / m to 7020μm / m, and the autogenous shrinkage decreases from 2924μm / m to 2387μm / m. The autogenous shrinkage of Example 22 is 1680μm / m, which is 42.54% lower than that of Example 18. The reason for the above differences is that the calcium carbonate whiskers overlap each other inside the matrix to form a "fibrous skeleton", which plays the role of a "support phase". When the matrix is subjected to compressive stress, it can share part of the stress, thereby achieving the effect of improving the compressive strength of the matrix. Micron-sized calcium carbonate whiskers act as a "restricting phase" in the system to limit shrinkage. The whiskers are evenly dispersed in the matrix. When the matrix shrinks due to internal stress, the internal friction generated by the close combination of the whiskers and the matrix offsets part of the shrinkage stress inside the matrix, thereby achieving the effect of reducing shrinkage.
[0131] Comprehensive analysis shows that the slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement prepared in Example 19 has the best performance, with initial and final setting times reaching 412 min and 429 min respectively, and 28-day compressive strength reaching 102.2 MPa. The 49-day drying shrinkage and autogenous shrinkage can be reduced by 15.52% and 18.37% respectively compared with Example 18.
[0132] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A slow-setting, shrinkage-reducing alkali-activated slag-calcined coal gangue cement, characterized in that: The invention comprises the following raw materials: slag, calcined coal gangue fine powder, calcium carbonate whisker and mixed alkaline activator; wherein the mixed alkaline activator is prepared by mixing water glass solution, sodium hydroxide and sodium carbonate.
2. The slow-setting, shrinkage-reducing alkali-activated slag-calcined coal gangue cement according to claim 1, characterized in that: The mass ratio of the slag to the calcined coal gangue fine powder is (70-85): (15-30); and / or The replacement rate of the calcium carbonate whiskers for slag is 3-12wt%.
3. The slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement according to claim 2, characterized in that: The parameters of the slag are: density 2.5-3.0g / cm 3 , specific surface area 610-630m 2 / kg, CaO content 30-40%, SiO2 content 25-35%; and / or The preparation method of the calcined coal gangue fine powder is as follows: washing, crushing and ball milling the original coal gangue to obtain coal gangue fine powder with a particle size of less than 0.075 mm, placing the powder in a box-type resistance furnace, heating it to 750° C. at 5° C. / min, and then keeping the temperature for 4 hours, and then sieving it through a 200-mesh square hole sieve after cooling; and / or The parameters of the calcium carbonate whiskers are: relative density 2.5-3.0g / cm 3 , aspect ratio 20-30, CaO content 80-90%, elastic modulus 650-750GPa.
4. The slow-setting, shrinkage-reducing alkali-activated slag-calcined coal gangue cement according to claim 1, characterized in that: The amount of the mixed alkaline activator is 65-75% of the total mass of the slag, the calcined coal gangue fine powder and the calcium carbonate whisker.
5. The slow-setting, shrinkage-reducing alkali-activated slag-calcined coal gangue cement according to claim 4, characterized in that: The preparation method of the mixed alkaline activator is as follows: adding sodium hydroxide to a water glass solution and stirring until dissolved; adding sodium carbonate to water and stirring until dissolved; mixing the two solutions to obtain the mixed alkaline activator, and standing it for more than 24 hours before use.
6. The slow-setting, shrinkage-reducing alkali-activated slag-calcined coal gangue cement according to claim 5, characterized in that: The parameters of the water glass solution are: modulus 2.4, chemical composition 32.35% SiO2, 13.73% Na2O and 53.92% H2O; and / or The sodium hydroxide is analytically pure, with a NaOH content of ≥96%; and / or The sodium carbonate is analytically pure, with a Na2CO3 content of ≥99.8%; and / or The mass ratio of the sodium carbonate, sodium hydroxide and water glass solution is (32-39): (2-4): (59-66).
7. A method for preparing the slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement according to any one of claims 1 to 6, characterized in that: The following steps are involved: The slag, calcined coal gangue fine powder and calcium carbonate whisker are mixed and dry-mixed until uniform, and then a mixed alkaline activator is added and continued to be stirred uniformly. The obtained cement paste is solidified and cured to obtain slow-setting and shrinkage-reducing alkali-activated slag-calcined coal gangue cement.
8. Use of the slow-setting, shrinkage-reducing alkali-activated slag-calcined coal gangue cement as claimed in any one of claims 1 to 6 in the field of building materials.
Citation Information
Patent Citations
Alkali slag concrete composite activator and preparation method of concrete mixture
CN106045361A
Preparation method of high-activity red mud-based concrete admixture
CN118221370A